Becoming Scholarly Writers: An Autoethnography of Three Emerging Scholars - Claire Kostopulos; Sunny L. Munn; Suzanne J. Gallagher (Adult Education Research Conference, 2007)
Two doctoral students and a new academic use autoethnography to reflect on their experiences as emerging scholars. Five themes are explored: developing mentor relationships, discovering and expressing one’s voice when writing, writing collaboratively, receiving and integrating constructive criticism, and using resources. Implications for adult education are also provided.